Предмет: Математика,
автор: 171116dimentra66
решите уравнение f'(x)=0 f(x)=x3+3x2+3x+1
Ответы
Автор ответа:
14
f(x)=x³+3x²+3x+1
Найдем производную:
f'(x)=3x²+6x+3
f'(x)=0 => 3x²+6x+3=0
3(x²+2x+1)=0
3(x+1)²=0
откуда х= -1
Ответ : х= -1
Найдем производную:
f'(x)=3x²+6x+3
f'(x)=0 => 3x²+6x+3=0
3(x²+2x+1)=0
3(x+1)²=0
откуда х= -1
Ответ : х= -1
Похожие вопросы
Предмет: Физика,
автор: Аноним
Предмет: Математика,
автор: Lolt0p
Предмет: Английский язык,
автор: Domashkaopr
Предмет: Алгебра,
автор: Аноним
Предмет: Алгебра,
автор: mariastarosta